Caring for America home health workers in the shadow of the welfare state - Boris, Eileen, 1948-; Klein, Jennifer, 1967- (Oxford : Oxford University Press, 2012)
This title is the definitive history of care work and its surprisingly central role in the American labour movement and class politics from the New Deal to the present. The authors create a narrative of the home care industry that interweaves four histories and considers their impact on today's most dynamic social movements.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Includes index.
Keywords: Home health aides -- United States; Home health aides -- Labor unions -- United States